KOMPARASI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TIPE JIGSAW DALAM PEMBELAJARAN SEJARAH PADA SISWA KELAS XI SMA NEGERI 1 ANGKOLA BARAT - Salman Al Paris Sormin (Jurnal Education and Development, 2018)
This study aims to determine differences of historical learning outcomes with the application of cooperative learning type STAD and Jigsaw in learning history in Class XI SMA Negeri 1 Angkola Barat. Population in this research is class XI SMA Negeri 1 Angkola Barat. The sampling technique used in this study using cluster sampling technique is obtained class XI IPS as a sample of 64 people. Data analysis techniques used in this study is descriptive data analysis to see the state of variable research and statistical data analysis to test the research hypothesis by using t-test. Based on the results of research that has been done to get the picture that, the learning outcomes history using STAD type cooperative learning model obtained an average value of 75.37 "good" category, while the students' learning outcomes using Jigsaw type obtained an average value of 65 , 97, category "enough". While the result of the hypothesis test is obtained t0 value of 11.21 while the value of t-table with 5% significance level obtained by 2.00. So if consulted then the value of t0> t table is 11.21> 2.00 means the alternative hypothesis proposed in this study can be accepted, in other words there are differences in historical learning results using STAD type cooperative learning and Jigsaw in history learning. The results of this study can be concluded that the first application of cooperative learning type STAD and Jigsaw can improve student learning outcomes. Second, STAD type in teaching history especially on Indonesian proclamation material is more suitable than Jigsaw type. Third, the alternative hypothesis is acceptable meaning that there are differences in historical learning outcomes by using STAD type cooperative learning model and Jigsaw type in history learning.